Feasibility of using sodium alginate for improving structural quality of sweet dahi (Bangladesh Journal of Animal Science, 2016)
Dahi is a popular fermented milk product with higher nutritional value and significant therapeutic properties. The objective of the present study was to use sodium alginate as stabilizer to monitor the feasibility of using for improving structural quality of sweet dahi. Dahi were prepared using 0.4%, 0.6%, 0.8% and 1% sodium alginate. One control sample was made with no stabilizer to judge the other treated samples. All the samples were analyzed for organoleptic and chemical qualities .Significant difference was found in case of smell & taste score (p